Pelo fio de Ariadne: uma proposta hipertextual para o ensino-aprendizagem de linguas estrangeiras modernas - Pereira, Talismara (2013)
The dissertation called Through Ariadne s yarn: a hypertextual proposal for the foreign language teaching-learning process, demands to deliniate another way of teaching foreign language, through the use of digital communication technology, where educators are encouraged to rethink their educational praxis in several senses but especially in harmony with the possibilities that digital technology offers. It searches to establish other treatments for foreign language teaching, since learnes find possibilities of accessing the foreigh language outside school, in a variety of ways, but specially on the internet. It deals with investigating the way that these languages are being taught in school, often in a descontextualized, hierarchical and arborous way. It offers as a contribution to foreign language teaching some yarn-paths, yarn-strategies, yarn-theoretical, yarn-reflections, yarn-transdisciplinarity and interdisciplinarity, yarn-meaninful learning in order to present a different, creative and reflective work, considering aspects that seduce, attract, re-enchant the learners to the continuous search for knowledge each day more vast, comprehensive and relevant to attend the requirements of a world in quickly transformation, pointing to the importance of foreign language teachers continuing education, offering moments for discussions, learnings and reflections. It presents possibilities for a hypertextual teaching through the use of digital technology in foreing language learning, which composes besides studies and researches, a continuing education course for foreign language teachers from public schools called atelier, where teachers were encouraged to act as learners in continuous exchange of experiences and knowledge while course participants and with their students, when they are at school, considering several paths to practice the foreign language in the digital environment, such as today's society requires